Zero-Outage Secrecy in Short Packet IoT-Aided Cellular Cooperative Network With EH-NOMA - Hien Quang Ta; Nga B. T. Nguyen; Tien-Tung Nguyen; Khuong Ho-Van (IEEE Access)
The zero-outage secrecy with energy harvesting is considered in short packet IoT-aided cellular cooperative networks using the inspired non-orthogonal multiple access (NOMA) strategy. The scheme ensures zero-outage secrecy through two cooperative transmissions: one for only artificial noise (AN) and another for both the artificial noise and the secure message. To ensure that only legitimate users can decode the message while the eavesdropper’s probability of success remains zero, which is so-called zero-outage secrecy, the scheme additionally employs the reverse training strategy to prevent the channel state information leakage to the eavesdroppers. The results show that the proposed scheme can achieve zero-outage secrecy for both IoT and cellular messages even in the case the eavesdroppers take advantage in their location or large number of antennas so that their channels become powerful. When forwarding the secure cellular message, the controller IoT node imposes the IoT message using such a large amount of harvested power that the IoT user can achieve the highest zero-outage secrecy throughput and energy efficiency, there is not much loss in the zero-outage secrecy throughput obtained at the cellular user. It also highlights that when the transmit power increases, the zero-outage secrecy throughput also increases, indicating the practical implementation of the proposed scheme.